A narrative approach to social media mourning : small stories and affective positioning - Giaxoglou, Korina (New York, NY : Routledge, 2021)
This book investigates how social media are reconfiguring dying, death, and mourning. Taking a narrative approach, it argues that dying, death, and mourning are shared online as small stories of the moment, which are organized around transgressive moments and events with motivational, participatory, or connective scope. Through the different case studies discussed, this book presents an empirical framework for analyzing small stories of dying, death and mourning as practices of sharing which become associated with specific modes of affective positioning, i.e. modulations of different degrees of distance or proximity to the death event and the dead, the networked audience(s), and the affective self. The book calls for the study of affect as integral to narrative activity and opens up broader questions about how stories and emotion are mobilized in digital cultures for accruing audiences, value (social or economic), and visibility. It will be of interest to researchers in narrative analysis, the anthropology and sociology of emotion, digital communication, media and cultural studies, and (digital) death and dying.
OCLC-licensed vendor bibliographic record.
Keywords: Death -- Social aspects; Grief -- Social aspects; Social media; Mourning customs; Narration (Rhetoric); Storytelling; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics